Analysis of Tax Compliance and Impacts on Regional Budgeting and Public Welfare - Simanjuntak, Timbul Hamonangan; Mukhlis, Imam (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
The research aims to analyze the impacts of tax compliance on regional budgeting and public welfare in East Java Province. Using the Partial Least Square (PLS) method, it considers the following variables: tax compliance, regional finance, general grant, special grant, regional expenditures, and Human Development Index (HDI). The results indicate that tax compliance has significant impacts on regional finance. Tax has significant positive impacts on regional expenditures/spending. Conversely, regional spending affects public social welfare in East Java Province. The research concludes that tax compliance gives significant positive impacts on public welfare in East Java Province during the 2004-2009 period. The prevalent policy implies that regional government has to secure regional financial balance to improve public welfare in East Java Province. The regional government is to promote public awareness that tax compliance is crucial to improve tax revenues and public welfare.